Time to death and its predictors among women with uterine rupture admitted to jimma town public hospitals, South West Ethiopia: retrospective cohort study - Lidetu Ababa Kenea; Chaltu Fikru Biyana; Buzuneh Tasfa Marine (BMC Pregnancy and Childbirth)
Abstract Background Uterine rupture is a public health issue in resource-limited countries, evidenced to account for 36% of maternal deaths in Ethiopia. This problem has not been studied in the study area, and little is known about the survival of women with uterine rupture. Therefore, this study aimed to assess time to death and its predictors among women with uterine rupture admitted to Jimma Town public Hospitals. Method An institution-based retrospective cohort study was conducted on all 405 eligible women with uterine rupture admitted to Jimma Town Public Hospitals. Data were collected by using structured questions developed in the Kobo toolbox and analyzed using Stata version 17. The Kaplan-Meier curve was used to estimate the median time to death, and a log-rank test was employed to assess statistically significant survival differences between groups. The Cox-proportional hazards model was fitted to identify predictors of the time to death. A hazard ratio with a 95% significance level and a P-value < 0.05 was considered to declare significant variables. Results From the total of 405 women followed for 4217 person-days, 38(9.4%) of them have died, leading to an incidence rate of 9 per 1000 women-days. The median survival time was 20 days. Hypovolemic shock (AHR: 3.87 (95%CI: 1.75, 8.53)), severe anemia (AHR: 3.56 (95%CI: 1.39, 9.12)), Not having ANC follow-up (AHR: 2.95 (95%CI: 1.02, 8.59)), admission at night time(AHR: 2.89(95%CI: 1.16, 7.76)), labour duration of ≥ 24 h (AHR: 2.69 (95%CI: 1.26, 5.78)) and having urine bladder rupture (AHR: 2.29(95%CI: 1.08, 4.91)) were predictors of time to death. Conclusion This study highlights the urgent need for improved healthcare interventions to address the issue of maternal death from uterine rupture and mitigate its impact on national maternal mortality rate. Timely and appropriate medical interventions are crucial in addressing the effects of factors such as hypovolemic shock, severe anemia, lack of ANC follow-up, labour duration of ≥ 24 h, night-time admissions, and urine bladder ruptures on maternal time to death when uterine rupture happens.